2023
DOI: 10.3389/fgene.2023.1131182
|View full text |Cite
|
Sign up to set email alerts
|

Paget’s disease: a review of the epidemiology, etiology, genetics, and treatment

Abstract: Paget’s disease of bone (PDB) is the second most prevalent metabolic bone disorder worldwide, with a prevalence rate of 1.5%–8.3%. It is characterized by localized areas of accelerated, disorganized, and excessive bone production and turnover. Typically, PDB develops in the later stages of life, particularly in the late 50s, and affects men more frequently than women. PDB is a complex disease influenced by both genetic and environmental factors. PDB has a complex genetic basis involving multiple genes, with SQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…In addition, germline mutations of zinc finger protein 687 ( ZNF687) and profilin 1 ( PFN1) genes are known to be associated with severe, early-onset polyostotic Paget disease of bone ( Gennari et al, 2022 ). Familial association has been demonstrated as well as an association with paramyxovirus based on occurrence of cytoplasmic and nuclear inclusions of virus in osteoclasts ( Banaganapalli et al, 2023 ). Histologically, the severity of the disease correlates with frequency of intranuclear inclusions.…”
Section: Endocrine/metabolic Related Craniofacial Deformitiesmentioning
confidence: 99%
“…In addition, germline mutations of zinc finger protein 687 ( ZNF687) and profilin 1 ( PFN1) genes are known to be associated with severe, early-onset polyostotic Paget disease of bone ( Gennari et al, 2022 ). Familial association has been demonstrated as well as an association with paramyxovirus based on occurrence of cytoplasmic and nuclear inclusions of virus in osteoclasts ( Banaganapalli et al, 2023 ). Histologically, the severity of the disease correlates with frequency of intranuclear inclusions.…”
Section: Endocrine/metabolic Related Craniofacial Deformitiesmentioning
confidence: 99%
“…Paget's disease of the bone (PDB) is the second most prevalent metabolic bone disorder worldwide, with a prevalence rate of 1.5%-8.3% characterized by disorganized bone remodeling as a result of fast bone resorption and bone formation by osteoclast and osteoblasts activity, respectively. [1][2][3] Along with long bone deformities, protruded foreheads, fractures, and hearing loss may occur. 4 In case of doubt, the diagnosis must be confirmed by radiographic modalities.…”
Section: Case Descriptionmentioning
confidence: 99%
“…Recent Genome Wide Association Studies (GWAS) identified susceptibility genes, loci and single nucleotide variants, including rs1561570 within the OPTN gene, rs484959 near the CSF1 gene, rs3018362 near the TNFRSF11A gene, rs5742915 within the PML gene, and others [ 1 ]. Another role in disease development may be played by epigenetic modifications of genes involved in bone metabolism such as RANKL (receptor activator of nuclear factor-kB ligand), OPG (osteoprotegerin), HDAC2, DNMT1, and SQSTM1 [ 10 ]. Among the environmental factors, we mention exposure to zoonoses (canine distemper) and viral infections (measles and respiratory syncytial virus), environmental toxins, vitamin D deficiency in childhood and skeletal injury, and repetitive mechanical loading [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mostly, they include: bone pain in the affected region; possible warmth and redness accompanying pain due to an increased vascularisation; bone enlargement and deformities such as bowing of the legs, skull enlargement, and kyphosis may be present; and the axial skeleton, which is most commonly affected. Other clinical elements are: constipation, abdominal pain, and hearing loss, as well as headache, especially related to skull involvement [ 10 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%